Pregnancy and after: what women want from their partners – listening to women in Uyo, Nigeria Read More: http://informahealthcare.com/doi/abs/10.3109/0167482X.2012.693551 - Udofia, E.A.; Akwaowo, C.D. (My University, 2012)
BACKGROUND: A qualitative survey was conducted among childbearing women at three public health facilities in Uyo, Nigeria. We aimed to determine (i) women's expectations of partner support during pregnancy and the postpartum period; (ii) predictors of partner presence during childbirth. METHODS: From May to mid-July 2011, 387 eligible women were recruited serially during visits to the child welfare clinic at each facility. Interviews were conducted using semistructured questionnaires. Responses were extracted and categorized into eight distinct themes with corresponding examples. RESULTS AND DISCUSSION: The most desired form of partner support was assistance with domestic chores during and after pregnancy; followed by financial support during pregnancy and providing/caring for the baby in the postpartum period. Partner support during pregnancy was high 98.0% (351). While 73% of respondents expected partner presence during childbirth, 69.4% reported actual partner presence. Women with no experience of pregnancy before marriage, a husband in formal employment, and regular assistance at home had a two- to three-fold likelihood of expecting partner presence at childbirth compared to those without these attributes. Expecting partner presence increased the likelihood of partner presence at childbirth. Results suggest that women have specific expectations of partner involvement during and after pregnancy.
Keywords: Childbirth, pregnancy, psychological well-being, women’s health